Numerical Study on Flame-Front Characteristics of Conical Turbulent Lean Premixed Methane/Air Flames - YILMAZ, BARIŞ; ÖZDOĞAN, ZEYNEP SİBEL (AMER CHEMICAL SOC, 2009)
Premixed turbulent methane/air flames with conical (or Bunsen) configuration are computed in two stages for selected equivalence ratios. First, the turbulent cold-flow field inside the combustion chamber is modeled, and turbulence characteristics are computed using the k-epsilon turbulence model and its variants. Second, the flame-front properties are investigated by two different turbulent premixed combustion models, namely, the Zimont model and the coherent flame model. All computations are per-formed with the Fluent software. The computations are confronted to the experimental data corresponding to turbulent flames in the corrugated flamelet regime. Experimental results concern turbulent premixed methane/air flames stabilized on a Bunsen-type burner; they are obtained mainly by LDA for the cold- and hot-flow velocity statistics and by laser-induced Mie and Rayleigh scattering techniques for flame-front statistics. The computations are in agreement with the experimental data; in particular, the decrease of both the flame height and the flame brush thickness with the increase of the equivalence ratio is well-reproduced by the computations.
Keywords: COMBUSTION; CLOSURE; MODEL